The social and lifestyle characteristics of sports bettors in Serbia - Dugalic, Stefan; Terzic-Supic, Zorica; Kilibarda, Biljana; Mravcik, Viktor; Stanisavljevic, Dejana; Stanisavljevic, Tamara; Piperac, Pavle; Todorovic, Jovana; Gojnic, Miroslava (Medical Research, 2022)
Aim: The aim of our study was to examine the prevalence of past month sports betting in Serbia and its association with social and lifestyle characteristics. Methods: The analysis of the data from the cross-sectional survey National Survey on lifestyles in Serbia: substance abuse and gambling conducted in 2014 was performed. 10% of participants reported sports betting in the past 30 days. Results: The sports betting was associated with being male, age, living in urban areas compared to living in rural areas, having secondary education compared to having primary education, being employed compared to being retired. Sports betting in the last 30 days was also associated with binge-drinking compared to abstaining from alcohol, non-prescription use of anti-anxiety medicationscompared to no use of anti-anxiety medications and low/ moderate, and problem gambling compared to no problem gambling as measured by PGSI, however, it wasnot associated with a higher risk of tobacco smoking and illicit drug use. Conclusions: The association of sports betting with risk behaviors among young males should be a concern for public health authorities. Keywords: sports betting; factors; gambling; problem gambling.